Estrutura de epífitas vasculares e de forófitos em formação florestal ripária do Parque Estadual do Rio Ivinhema, Estado de Mato Grosso do Sul, Brasil. - Tomazini, Vanessa (2007)
The purpose of this study was to carry a structural survey of the vascular epiphytes and phorophytes in a riparian formation of the Upper Paraná River floodplain. The study area is a remain forest, denominate Mata da Lagoa Finado Raimundo, localized in the Ivinhema River, Jateí, MS, Brazil (22º47'21''S e 53º32'04''W). Were realized floristic survey of epiphytes in area of the approximately 888,500 m2, comprehensive all remanescent. The structural survey of phorophyte and epiphytes were realized in total area of 8,100 m2, subdivided in nine blocs distributed in tree transepts. Every bloc was arranged in nine continuous quadrates of 10 x 10 m, in that were realized phytosociological survey in the same moment this survey, with objective of quantify all individuals of component arbutus-arbores and arbores with PAP ≥ 15 cm. To estructural survey were observed all the individuals registred in phytosociological survey that were colonized for epiphytes and, the representativeness of phorophytes were analyzed for comparison with category no-phorophytes. Were analyzed, too vertical and horizontal distributions of epiphytes and, Valour Epiphytic's Importance obtained for values of frequency de every epiphytic specie in relation number of phorophytes individuals and stratus (2 m amplitude). In the floristic survey were recorded 29 species, 20 genera and five families of epiphytes. Orchidaceae and Bromeliaceae were the richest families, with 60.0% of genera e 65.5% of species. The phorophytes abranged 45 species, 35 genera and 21 families. Leguminosae and Myrtaceae were the richest families with 31.4% of genera and 33.2% of species. The phorophytes individuals abranged, respectively, 41.73%, 17.2% and 42.2% of relatives frequency, density and dominancy, and 33.7% do IV of study area. Zygia caulifloria (Willd.) Killip ex Record presented largest density of phorophytes individuals (34.1%) and epiphytic species (75.0%). The number of epiphytic species in one phorophyte varied from one to 10 (average of 1.83 ± 1.38), with Shannon's Index of Diversity equal 2.24. The canopy and interval of 2-6m high were predominat, with respectively, 75.9% and 54.8% of epihytics occurrences. Microgramma vacciniifolia (Langsd. & Fisch.) Copel. (88.9), Peperomia pereskiaefolia H.B. & K. (22.2), Macradenia multiflora Cogn. (16.2), Oncidium pumilum Lindl. (13.1) and Rhipsalis baccifera (Mill.) Stearn (13.1) showed the most IVi. The areas closed of flood's margin (opposed lagoon's margin) were more favorable epiphytes than the areas in lagoon's margin, probably because of minor edges effects. Despite of non significative the difference of epiphytic diversity this study with other remain forest in the Upper Paraná River floodplain, showed low floristic similarity of species, and largest high (stratus) of occurrence of epiphytes in forophytes, probably because of best preservation?s conditions. Macradenia multiflora, Oncidium pumilum, Peperomia pereskiaefolia and Rhipsalis baccifera are possible indicative of remain more conserved to the Upper Paraná River floodplain.